Nanoparticles and Radiotracers: Advances toward Radio-Nanomedicine - Pratt, Edwin C. (Wiley Interdiscip Rev Nanomed Nanobiotechnol, 2016)
Here, we cover the convergence of radiochemistry for imaging and therapy with advances in nanoparticle (NP) design for biomedical applications. We first explore NP properties relevant for therapy and theranostics and emphasize the need for biocompatibility. We then explore radionuclide-imaging modalities such as Positron Emission Tomography (PET), Single Photon Emission Computed Tomography (SPECT), and Cerenkov Luminescence (CL) with examples utilizing radiolabeled NP for imaging. PET and SPECT have served as diagnostic workhorses in the clinic, while preclinical NP design examples of multimodal imaging with radiotracers show promise in imaging and therapy. CL expands the types of radionuclides beyond PET and SPECT tracers to include high-energy electrons (β(−)) for imaging purposes. These advances in radionanomedicine will be discussed, showing the potential for radiolabeled NPs as theranostic agents.